Penerapan Algoritma Apriori Terhadap Data Penjualan Di Swalayan Koperasi Bappenas Jakarta Pusat - Siti Aisyah; Normah Normah (Paradigma, 2019)
Supermarkets are a place to supply daily necessities ranging from nine basic commodities to household needs. Every day there are several sales transactions, which that data will increase continue. Usually these sales data are only used as store archives, actually in sales data there are information that can be used to find out the most sales simultaneously so that a method is needed to find out which products has selling well using apriori algorithm and tools rapid miner help. From the results of analyzing the sales data, consumers who conduct basic needs product transactions obtained from the purchase of dominating item combinations are a combination of Indocafe Jar 200g and Kapal Api 165g items with the highest support value of 0,213. Then, the buyers of item combination which dominates Max Creamer 450gr item and Kapal Api 165gr confidence value are 0,958 and the buyrs combination of Gulaku Kuning and Kapal Api 165g support value are 0,259 From these results, concluded every consumer buys Indocafe Jar 200g there is an indication that consumers will also buying Api Kapal Api 165gr as well as Gulaku Kuning with Kapal api 165g and Max Creamer 450gr and Kapal Api 165gr.